Deteksi Cacing Capillaria hepatica pada Organ Hati Tikus - Supriadi Supriadi; Dina Oktaviana; Nofisulastri Nofisulastri (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Capillaria hepatica is a zoonotic parasitic agent that has been reported in various parts of the world. The presence of C. hepatica in an area is closely related to the presence of a rat population. Considering the life cycle of C. hepatica which is easily transmitted to humans, one of the most vulnerable places for transmission of C. hepatica to humans is the market area. This study aims to detect the presence of C. hepatica worms in the rat population in Public Market Kebon Roek, Ampenan District, Mataram City. This type of research is descriptive research with a cross sectional study design (cross-sectional study). To determine the number of samples, an accidental study approach was used, namely the number of rat samples used was the number of rats caught during the study period (set for 2 traps). 10 samples of rat liver were collected. The liver was then preserved in 10% formalin solution at the Microanatomy Laboratory, Department of Anatomy, Faculty of Veterinary Medicine, Gadjah Mada University. Meanwhile, histology preparations and GI fluid examination were carried out at the Clinical Skill Center (CSC) Laboratory, Faculty of Veterinary Medicine, Mandalika University of Education. Data in the form of images of worm eggs and histopathology of liver tissue were analyzed descriptively and presented in the form of figures and tables. The results of the examination of 10 samples of rat liver histology preparations showed that 4 positive samples contained eggs and adult worms of C. hepatica. Where the 3 histological preparations observed showed that the rat liver was severely damaged, and 1 sample appeared to have minor damage. For examination of gastrointestinal fluids, there were no samples containing C. hepatica worm eggs.